Review: Targeting the Transforming Growth Factor-Beta Pathway in Ovarian Cancer - Roane, Brandon M. (Cancers (Basel), 2019)
Despite extensive efforts, there has been limited progress in optimizing treatment of ovarian cancer patients. The vast majority of patients experience recurrence within a few years despite a high response rate to upfront therapy. The minimal improvement in overall survival of ovarian cancer patients in recent decades has directed research towards identifying specific biomarkers that serve both as prognostic factors and targets for therapy. Transforming Growth Factor-β (TGF-β) is a superfamily of proteins that have been well studied and implicated in a wide variety of cellular processes, both in normal physiologic development and malignant cellular growth. Hypersignaling via the TGF-β pathway is associated with increased tumor dissemination through various processes including immune evasion, promotion of angiogenesis, and increased epithelial to mesenchymal transformation. This pathway has been studied in various malignancies, including ovarian cancer. As targeted therapy has become increasingly prominent in drug development and clinical research, biomarkers such as TGF-β are being studied to improve outcomes in the ovarian cancer patient population. This review article discusses the role of TGF-β in ovarian cancer progression, the mechanisms of TGF-β signaling, and the targeted therapies aimed at the TGF-β pathway that are currently being studied.